Epidemiology and health services evaluation - doi:10.5020/18061230.2011.p151 - Dixis Figueroa Pedraza (Universidade de Fortaleza, 2012)
Objective: To discuss the application of Epidemiology in health services evaluation. Data synthesis: The contribution of Epidemiology in health services evaluation occurs mainly in the selection, construction and analysis of indicators and the assessment of performance and impact. Two basic axes guide health services evaluation: the type of indicator used and the degree of inference needed to conclude whether the results are due or not to intervention. The type of indicator to be used depends, essentially, on what is being measured, the process, the outcome or both. According to the degree of causal inference, there are three types of evaluation: adequacy, plausibility and probability. This paper presents the designs of studies that can be used in the evaluation of health services according to the degree of inference. Considering the conditions in which health services are structured and proceed, the studies of adequacy and plausibility are more convenient to evaluate the performance and impact of health services. Conclusions: There are still important methodological problems that must be overcome in the impact assessment of public health interventions. These problems include the difficulty associated with randomization, obtaining control groups for confounding factors and the choice of relevant indicators of process and outcome.